Adsorption of hazardous chromium (VI) ions from aqueous solutions using modified sawdust: kinetics, isotherm and thermodynamic modelling. Issue 7 (28th May 2021) - Chakraborty, Rupa; Verma, Renu; Asthana, Anupama; Vidya, S. Sree; Singh, Ajaya Kumar
ABSTRACT: The presence of chromium in aquatic streams due to the discharge of industrial effluents is of great concern because of its toxic nature. Removal of Cr(VI) ion from wastewater is a necessary task. To enhance the adsorption capacity of sawdust for heavy metals, sawdust was modified with formaldehyde and used for the adsorption of heavy metal Cr(VI). The process of modifying was characterised by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The effects of various parameters such as pH, contact time, adsorbent dose and initial metal ion concentration on the adsorption process were investigated. The maximum removal of chromium (VI) was found to be 100% at pH 2.0, initial Cr(VI) concentration of 10 mg/L, and adsorbent dose of 4 g/L. Equilibrium isotherms for the removal of Cr(VI) were analysed by the Langmuir, Freundlich, and Temkin isotherm models and the experimental data were well explained by the Freundlich isotherm model. The maximum adsorption capacity was found to be 8.84 mg/g. Kinetic studies were performed by pseudo-first-order, pseudo-second-order, intraparticle diffusion and Elovich models. The R 2 value of the pseudo-second-order model is higher than other kinetic models. Therefore, the obtained data were the best fit with the pseudo-second-order kinetic model. The thermodynamics indicated that the adsorption process of sawdust for Cr(VI) was endothermic and spontaneous in nature.